2021
DOI: 10.3389/fphys.2021.719580
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Three Preseason Training Programs on Speed, Change-of-Direction, and Endurance in Recreationally Trained Soccer Players

Abstract: Background: Modern coaches experience a drastic reduction of the available training time with an increasingly large number of competitions during the competitive season. Thus, they must choose wisely the most efficient methods to improve the physical fitness of their players during the preseason. Among all the methods, this study compared the effects of plyometric training (PT), sprint interval training (SIT), and small-sided games (SSGs) on the performance of recreationally trained soccer players.Methods: Sev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 76 publications
0
6
0
Order By: Relevance
“…The inclusion of studies conducted across different stages of the season provides valuable representativeness in terms of seasonality. Within the analyzed research, studies were identified that focused exclusively on the pre-season [72,73,77], first half of the competitive season [36,70,85,86], second half of the competitive season [74,[87][88][89], and post-competitive season [37]. Additionally, some studies examined combined periods, such as pre-season and early competitive season [71,90].…”
Section: Methodological Characteristics Of Training Interventions: a ...mentioning
confidence: 99%
See 4 more Smart Citations
“…The inclusion of studies conducted across different stages of the season provides valuable representativeness in terms of seasonality. Within the analyzed research, studies were identified that focused exclusively on the pre-season [72,73,77], first half of the competitive season [36,70,85,86], second half of the competitive season [74,[87][88][89], and post-competitive season [37]. Additionally, some studies examined combined periods, such as pre-season and early competitive season [71,90].…”
Section: Methodological Characteristics Of Training Interventions: a ...mentioning
confidence: 99%
“…Regarding moderator analyses according to the type of HIIT intervention, similar changes in the field-based tests performance were noted after HIIT-RST (3 groups; ES = 0.86, 95% CI = -0.41-2.13; I 2 = 81.6%), HIIT-long intervals (4 groups; ES = 0.40, 95% CI = -0.47-0.54; I 2 = 27.0%), and HIIT-short intervals (7 groups; ES = 0.16, 95% CI = -0.21-0.53; I 2 = 32.0%), with a between-moderator category p value of 0.498. Of note, the studies from Koral et al [73] and from Castillo et al [74] were not included in the analyses as only 1 trial was available per each HIIT type.…”
Section: Accepted Manuscriptmentioning
confidence: 99%
See 3 more Smart Citations